Reuters Institute digital news report 2020 - Newman, N; Fletcher, R; Schultz, A; Andi, S; Nielsen, RK (Reuters Institute for the Study of Journalism, 2020)
The ninth Digital News Report from the Reuters Institute for the Study of Journalism at the University of Oxford reveals new insights about digital news consumption based on a YouGov survey of over 80,000 online news consumers in 40 markets including Kenya and the Philippines for the first time. The report looks at the impact of coronavirus on news consumption and on the economic prospects for publishers. It looks at progress on new paid online business models, trust and misinformation, partisanship and populism, and the popularity of new curated editorial products like podcasts and email newsletters.